Galacto-Oligosaccharides - Vera-Vera, C (Springer International Publishing, 2023)
Prebiotics are important components in functional foods. Galactooligosaccharides (GOS) are nondigestible oligosaccharides whose prebiotic condition has been conclusively proven. GOS are produced from lactose, which is a cheap commodity, usually in surplus from the cheese manufacturing industry. GOS synthesis is catalyzed by B-galactosidases that are cheapenzymes with a long record of use in the food industry for the production of low-lactose milk and dairies, so its use for GOS synthesis represents a remarkable technological opportunity. GOS have salient features that make them ideal for their incorporation into functional foods, especially in dairy products, so that a scheme of circular economy can be envisaged. Even though GOS production is well established at industrial level, several challenges remain that are related to the rather low yield of the kinetically controlled reaction of synthesis from lactose. This results in poor substrate utilization and complex downstream operations, so major efforts are devoted to developing better suited enzymes and cheaper and simpler downstream operations. This chapter focuses on GOS production within the framework of functional foods, with special emphasis on technological perspectives of their production, but basic aspects, like reaction mechanisms and mode of prebiotic action, are also revised. © Springer Nature Switzerland AG 2023.